The effect of using the K.W.L strategy in acquiring health concepts in the social education subject for eighth graders in Jordan - Obeidat, Dima Adnan Rushdi (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the effect of using the K.W.L strategy in acquiring health concepts in the social education subject for eighth graders in Jordan. The researcher used the quasi-experimental approach to identify the effect of using the K.W.L strategy in acquiring health concepts in the social education subject. The researcher prepared a test to measure the health concepts of the study sample, which consisted of (68) students in two groups (control – experimental). The study reached several results, the most important of which are: There is an effect of K.W.L's strategy in acquiring health concepts in the social education subject for eighth grade students in Jordan, where the experimental sample outperformed the control sample. The study recommended the necessity of using the K.W.L teaching strategy in all units of the social education subject.
Keywords: multiple intelligences; health concepts; social education books